2019
DOI: 10.2337/dc18-1841
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of a Tailored Cognitive Behavioral Intervention in Type 2 Diabetes With Comorbid Depressive and/or Regimen-Related Distress Symptoms: 12-Month Outcomes From COMRADE

Abstract: OBJECTIVEThis study evaluated the effect of cognitive behavioral therapy (CBT) plus lifestyle counseling in primary care on hemoglobin A 1c (HbA 1c ) in rural adult patients with type 2 diabetes (T2D) and comorbid depressive or regimen-related distress (RRD) symptoms. RESEARCH DESIGN AND METHODSThis study was a randomized controlled trial of a 16-session severity-tailored CBT plus lifestyle counseling intervention compared with usual care. Outcomes included changes in HbA 1c , RRD, depressive symptoms, self-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 29 publications
0
57
0
Order By: Relevance
“…Eight of the twelve trials studies in that meta-analysis were involved in CBT and all eight reported improvement in long-term glycemic control and reduction of psychological distress in the CBT groups [32]. Similarly, several previous studies, e.g., Cummings et al [24], evaluated the effect of cognitive behavioral therapy (CBT) plus lifestyle counseling in primary care on HbA1c levels in rural adult patients with T2DM with comorbid depressive and/or medication adherence behavior-related distress symptoms. The Cummings study found that patients in the intervention group showed significant improvement in HbA1c levels and greater improvement in DRD compared to the group receiving standard care.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Eight of the twelve trials studies in that meta-analysis were involved in CBT and all eight reported improvement in long-term glycemic control and reduction of psychological distress in the CBT groups [32]. Similarly, several previous studies, e.g., Cummings et al [24], evaluated the effect of cognitive behavioral therapy (CBT) plus lifestyle counseling in primary care on HbA1c levels in rural adult patients with T2DM with comorbid depressive and/or medication adherence behavior-related distress symptoms. The Cummings study found that patients in the intervention group showed significant improvement in HbA1c levels and greater improvement in DRD compared to the group receiving standard care.…”
Section: Discussionmentioning
confidence: 53%
“…The present study found no significant differences in medication taking behavior or physical activity between the experimental group and control group, although medication taking behavior did improve in the experimental group. A study by Cummings et al [24] found that patients receiving CBT intervention evidenced significantly greater improvements in medication adherence than those receiving the usual care. There may be other factors, however, that affect medication taking behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…to improve effectiveness for Veterans with PTSD is warranted. Despite evidence-based programs to address weight 25 -27 and related conditions like diabetes 28 among individuals with other mental health conditions, there are no such programs for individuals with PTSD. Importantly, VA supports efforts to tailor MOVE!…”
Section: Purposementioning
confidence: 99%
“…2 Reducing diabetes-related distress may improve HbA1c and reduce the burden of disease among people with diabetes. 3,4 However, current diabetes management guidelines dedicate little attention to the prevention and management of diabetes-related distress. This is due, in part, to the limited knowledge of the sources of stress, anxiety and concerns among people with diabetes and to the difficulty to capture 5,6 them with existing evaluation scales such as the Problem Areas in Diabetes Scale (PAID or PAID-T for adolescents) 7 or the Diabetes Distress Scale (DDS).…”
Section: Introductionmentioning
confidence: 99%